Аналіз стану жіночого підприємництва в Україні в умовах війни - Лазоренко, Л.В. (Економічний вісник Донбасу, 2024)
В статті розкрито особливості жіночого підприємництва та його роль в Україні в сучасних умовах. Особливої актуальності воно набуває у воєнний час, оскільки, не зважаючи на те, що лідерами підприємницької діяльності продовжують залишатися чоловіки, жінки змушені провадити бізнес-діяльність, щоб підтримати суспільство, економіку держави, адже багато чоловіків повинні захищати нашу країни та вступати до лав ЗСУ. Гендерної відмінності в підприємництві особливо немає. Є певна специфіка. Жінки віддають перевагу малому бізнесу та окремим, ближчим і зрозумілішим їх видам діяльності таким, як бухоблік і аудит, сфера послуг, сфера торгівлі. З іншого боку, самі ці види діяльності приносять непоганий швидкий прибуток і є затребувані на ринку. До ознак, що вирізняють жінку-підприємця варто віднести наявність індивідуальної трудової діяльності, високу відповідальність у просуванні власної бізнес-справи, галузеву спеціалізацію. Особливістю жіночого підприємництва є те, що такий вид зайнятості дає можливість жінці вдало поєднати професійну діяльність та домашні обов’язки, контролювати свій час; вдало використовувати свої вміння, навички, знання, сприяє саморозвитку. Загалом же в Україні зареєстровано майже мільйон діючих комерційних компаній. Жінки є власниками більше 18% підприємств. 14% компаній є у спільній власності жінок та чоловіків. Найпопулярнішою діяльністю жіночого підприємництва є аудиту та бухобліку – понад 40% компаній належать жінкам, ще 20% у спільній власності. Також популярними такі види діяльності, як туризм, освіта, громадське харчування та легка промисловість. The article reveals the features of women's entrepreneurship and its role in Ukraine in modern conditions. It becomes especially relevant in wartime, because, despite the fact that men continue to be the leaders of entrepreneurial activity, women are forced to conduct business activities to support society, the economy of the state, because many men must defend our country and join the ranks of the Armed Forces. There is not much of a gender difference in entrepreneurship. There are certain specifics. Women prefer small businesses and separate, closer and more understandable types of activities, such as accounting and auditing, services, and trade. On the other hand, these activities themselves bring a good quick profit and are in demand in the market. Women entrepreneurs are a special social group of women, mainly from 25-50 years old, who have the social status of an entrepreneur, have value orientations, worldview, interests, needs and socio-psychological properties due to the transforming society. The features that distinguish a woman entrepreneur include the presence of individual labor activity, high responsibility in promoting her own business, industry specialization. The peculiarity of women's entrepreneurship is that this type of employment allows a woman to successfully combine professional activity and household duties, to control her time; successfully use their skills, abilities, knowledge, promotes self-development. In total, almost a million operating commercial companies are registered in Ukraine. Women own more than 18% of enterprises. 14% of companies are jointly owned by women and men. The most popular activity of women's entrepreneurship is audit and accounting – more than 40% of companies are owned by women, another 20% are jointly owned. Activities such as tourism, education, catering, and light industry are also popular. Among the main problems of women's entrepreneurship are: the consequences of the economic crisis, high competition, frequent and unpredictable changes in legislation, state regulation, tax system, possible interruptions in communication, the Internet, electricity, corruption.